Электронный прибор для исследования психофизиологических показателей человека - Фирсов, А. Г. (ХНУРЕ, 2008)
We describe a new device for research of some psycho physiological reaction of operator - man. The device allows measure critical frequency of the flashing confluence, dark adaptation time and response time. The device can connecting to PC for automatic measurement
Keywords: психофизиологические показатели человека; исследование показателей человека